(untitled) (Research, Society and Development, 2023)
Introduction: Undergraduate students face significant mental health issues during Higher Education, such as depression, anxiety and stress. In this sense, it is thought that sessions of choir singing can softy these issues. Methodology: This study analyzed the levels of depression, anxiety and stress in undergraduate students after four weekly choir singing sessions. Forty-five participants answered the questionnaire of sociodemographic conditions and the Depression, Anxiety and Stress Scale (DASS-21). The data obtained was statistical analyzed. Results: The analysis did not observe statistical significance (p<0.05), however, the values showed clinical relevance. High frequencies of severe symptoms of anxiety (24.5%), depression (31.2%) and stress (24.5%) were observed in the last week of the study, 24.4% of the participants had two or more severe symptoms in the last week of the study and there was a high mean of the scores for those who presented two or more severe symptoms. The gender variable indicated higher levels of anxiety (28.6%), depression (42.9%) and stress (42.9%) in men. The color variable identified higher levels of anxiety (31.6%), depression (47.4%) and stress (31.6%) in black. Discussion: High values were observed in university students even after four choir singing sessions and these levels were higher in male and black students. Conclusion: Due to the clinical relevance, further studies may be conducted with the analysis of different variables, in order to expand the knowledge related to the benefits of choral singing and to mitigate mental health issues during Higher Education.